Kentsel Yaşamda Aydınlatmanın Önemi Ve Aydınlatma Problemlerinin Tespiti: İTÜ Ayazağa Yerleşkesi Örneği - Alpaslan, Şeyma (Fen Bilimleri Enstitüsü, 2015)
Kentlerde,  fiziksel, ekonomik ve doğal çevreyi ilgilendiren en önemli düzenlemelerden biri aydınlatma tasarımıdır. Aydınlatma, insanların yaşam kalitesine sahip olabilmeleri için ihtiyaç duydukları güvenliğin sağlanmasında ve estetik gereksinimlerinin karşılanmasında büyük öneme sahiptir. Doğru bir kentsel aydınlatma sayesinde kentlilerin ihtiyaçları karşılanarak, kentsel yaşam kalitesi arttırılmış olacaktır. Doğru bir kentsel aydınlatma; aydınlatma kriterlerine uygun olarak, teknik ve estetik yönden birlikte ele alınıp, çevre ile uyumu gözetilip, görsel ve işlevsel açıdan başarılı bir şekilde gerçekleştirilmelidir. Gerekli aydınlatma kriterlerine dikkat edilmeden uygulanmış olan aydınlatma sistemleri ise kentsel mekânlarda bir takım sorunlara yol açmaktadır.  Bu sorunlardan biri ışık kirliliğidir. Işık kirliliği; genel olarak ışığın, yanlış yerde, yanlış miktarda, yanlış yönde ve yanlış zamanda kullanılması olarak tanımlanmaktadır. Işık kirliliği, doğal hayatı, insanların günlük yaşantılarını, kent ekonomisini ve astronomik gözlemleri olumsuz etkilemektedir. Bunlar da kentsel yaşam kalitesini düşüren önemli unsurlardır. Diğer bir problem, kentlerdeki aydınlatma yetersizliğidir. Yetersiz aydınlatma, kentsel mekânda görme eyleminin sağlıklı bir şekilde gerçekleştirilebilmesi için ihtiyaç duyulan aydınlatma seviyesinin altında olması veya aydınlatmanın hiç olmamasıdır. Kentsel mekânlarda aydınlatmanın yetersiz olmasıyla çevresel algı problemleri ve güvensizlik hissi oluşmaktadır. Kentsel aydınlatmada karşılaşılan bir diğer problem ise; aydınlatma sistemlerindeki bakımsızlıktır. Bakımsız aydınlatma sistemlerinde; zamanla özelliklerini kaybeden lamba ve armatürlerin verimliliği azalarak, enerji israfına ve yetersiz aydınlatma problemlerine yol açar.  Kentsel mekânlarda sıklıkla karşılaşılan bu problemlerin tespit edilmesi ve ortadan kaldırılması için çeşitli önlemlerin alınması gerekmektedir. Problemlerin tespiti için dünyada yapılan çalışmalar incelendiğinde dört ana yöntem olduğu tespit edilmiştir. Bunlar; kentsel mekânın havadan fotoğraflanması, ışık ölçer ile kentsel mekândaki aydınlık düzeylerinin ölçümü, kentsel mekânda yapılan gözlemler ve kentsel mekânın kullanıcılarıyla yapılan anket çalışmasıdır.  Tez çalışmasında, bu araştırma yöntemlerini kullanarak, kentsel aydınlatma sistemlerinde rastlanan problemleri ortaya çıkartmak amacıyla İstanbul Teknik Üniversitesi (İTÜ) Ayazağa Yerleşkesi incelenmiştir. Çalışmada, ışık ölçer cihazı ile aydınlık değerleri elde edilmiş; bu değerler, gözlem ve anket çalışmalarından gelen sonuçlarla bir araya getirilerek, aydınlatma problemleri tespit edilmiştir.  Tüm bu incelemeler sonunda görülmüştür ki; İTÜ Ayazağa Yerleşkesi, ışık kirliliği, yetersiz ve  bakımsız aydınlatma gibi problemlerle karşı karşıyadır. Bu problemlerin çözülerek yerleşkedeki kentsel yaşam kalitesinin arttırılması; armatür tiplerinde gerekli olan düzenlemelerin yapılması, geceleri hiç aydınlatılmamış olan bölgelere aydınlatma projelerinin hazırlanması ve mevcut aydınlatma sistemlerine bakım yapılması ile mümkündür. Yerleşkenin daha başarılı bir aydınlatma sistemine sahip olması için ise, aydınlatma standartları göz önünde bulundurularak hazırlanan aydınlatma master planına ihtiyaç duyulmaktadır. Bu sayede, İTÜ Ayazağa Yerleşkesi kullanıcılarının görsel konforu sağlanmış ve yaşam kaliteleri arttırılmış olacaktır.

Urban quality of life can be defined as a combination of housing, security, lack of stress, inter-personal relations, education, health, recreation, personal independency, and human rights. It can influence the sustainability and welfare of communities and has therefore become an important research subject in the area of urban planning. A very important contributor to urban quality of life is urban lighting. The element of lighting has great importance when designing cities, with effects on the physical, economic and natural environment. From an architectural and aesthetic point of view, urban lighting improves visual comfort at night, and from a functional point of view, provides the security of citizens. Therefore, correct urban lighting provides people’s needs and improves quality of life.  Human beings perceive their physical surroundings by their light, color, sound, heat, humidity and smell. Vision is a lot more helpful than other senses in one’s perception of environment, so light is the most important of these factors. During daytime, illuminance from the sun provides our lighting, but at night, light reflected by the moon is not enough for our daily routines. Our ability to have daytime vision at night depends mostly on artificial lighting technologies. Providing adequate lighting for people to carry out their visual tasks makes up only one component of urban lighting. Other factors such as illuminance, luminance distributions, light color characteristics and reflection should also be considered. Optimal lighting can only be achieved if technology is combined with aesthetics to produce visual and functional perfection compatible with the environment. Lighting systems in urban areas can cause problems if designed and installed without regards for the necessary lighting criteria, or if not maintained properly. One of these problems is light pollution. Light pollution is generally defined as the use of light in the wrong place, amount, direction or at the wrong time. It has negative effects on nature, people’s everyday lives, urban economy and astronomical observations. Too much lighting or over-illumination in cities may disrupt natural animal behavior. The lives of animals that depend on Earth’s daily cycle of light and dark to govern life-sustaining behavior, such as birds and turtles, are therefore threatened. Although people need a certain level of lighting at night to be able to see clearly, nighttime illumination similar to daytime measures has negative effects on human health. We are recommended to sleep in darkness and chronic exposure to light at night may lead to health problems. Over illumination of cities also affect urban economies by increasing energy costs. A significant amount of energy loss in cities is due to over illumination. Finally, light scattered to the sky has negative effects on astronomical sciences. Stars and celestial bodies cannot be visualized in a light sky, which hinders astronomical studies. All of these factors lead to a decreased urban life quality. Another problem is inadequate lighting in cities. Inadequate lighting can be defined as below required illumination levels for good vision or total lack of light. In urban areas, inadequate lighting can cause problems of environmental perception and the feeling of insecurity. Visual discomfort and misperception hamper urban quality of life by decreasing the “readability” of the city. In addition, crime rates seem to increase in urban areas with insufficient lighting. As a result, people using these areas feel insecure, causing them to be dissatisfied with the city. This dissatisfaction eventually diminishes the sense of belonging, which should be avoided to improve the sustainability of cities. Maintenance of lighting systems is also an issue in urban lighting. Neglected lamps and armatures lose efficiency over time, resulting in energy loss and inadequate lighting. In addition, neglected armatures cause an unpleasant sight.  Armatures in need of repair next to working ones cause diversity and disorder.  These three main problems in urban areas need to be identified and appropriate measures be taken for their prevention. In literature, we see mainly four methods for problem identification. They are: taking air photographs of the urban space, measuring lighting levels using a light meter, making observations in the urban area and interviewing users of the area.  The method of air photography includes analyzing nighttime lighting using satellite pictures of urban areas or pictures taken from a helicopter. The light meter method is performed by measuring lighting levels at specified points of the urban area. The acquired values are then inserted in a computer software program to form a lighting map, which can be used to identify problems in lighting. In the method of observational analysis, the researcher makes observations in the study area and identifies the problems s/he beholds. Finally, it is possible to question the users of an urban area for lighting problems they face or observe.  In this study, Istanbul Technical University (ITU) Ayazaga Campus was analyzed using these four methods to identify problems in urban lighting systems. Illumination levels were obtained using a lux meter and research was conducted using observations and surveys to identify the problems in lighting. A computer program was then used to convert the lighting data into a map showing lighting levels. The lighting map plays a very important role in identifying lighting problems. Data from the observational analysis were combined, revealing characteristics of lighting armatures, their effects on night vision, locations in the area, conditions, and adequacy. Finally, lighting problems observed directly by its users, their needs and opinions were questioned and added to the data. ITU Ayazaga campus is considered the center of one of the most prestigious universities of Turkey. It is a semipublic urban space used by thousands of students and campus lighting affects their quality of life. The analysis of the acquired data has shown the campus is facing lighting problems. They are; light pollution due to over illumination, inadequate lighting with dark or poorly lighted areas, and neglected lighting with some useless armatures damaged over time and armature diversity, where groups of armatures were replaced at separate times. Solutions were proposed in order to overcome these problems. For visual comfort, the lighting level ratio of the view point to surroundings should not exceed 1/20. Lighting systems must be installed in dark areas and the lighting levels in dark areas should be increased to an average of 30-40 lx for security purposes. Especially shuttle stops and the lake area need better lighting for functional purposes. Since the Bosporus and city lights can be seen from this side of the campus, armatures lower in height should be chosen in order to avoid too much glare. Height of the armatures should be adjusted and indirect lighting should be preferred over direct lighting to avoid light pollution. LED lighting systems are more efficient and sustainable, but metal-halide lamps and sodium vapor lamps can also be used as second choices. Instead of switching off lights in less-used spaces, motion detecting lighting systems can be preferred for conservation of energy. Lamps of various colors can be replaced to create a uniform light color. The lighting of statues, sports fields and the lake, however, may vary. The overall dominant color in the campus should be natural white, which is similar to daylight. In addition, current lighting systems must be maintained well. There should also be a lighting master plan in line with lighting standards. As a result, the visual comfort of ITU Ayazaga Campus users will be provided and their quality of life improved.
The Significance Of Lighting In Urban Life And The Analysis Of Urban Lighting Problems: A Case Study Of ITU Ayazaga Campus
(Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
(M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: kentsel yaşam kalitesi; kentsel aydınlatma; aydınlatma problemleri; İTÜ Ayazağa Yerleşkesi; urban life quality; urban lighting; lighting problems; ITU Ayazaga Campus